A Representação De Infância Nas Obras De Arnaldo Barreto Educar, Civilizar E Modernizar O Cidadão Republicano - Regina, Maria Silvana Benevides [UNIFESP] (2017)
The invastigation focus of this research is the childhood concieved, produced and registered at the text books of Arnaldo de Oliveira Barreto, that at the end of the 19th century and begging of the 20th century, occupied important roles and exercised relevant function in the instruction and education of children. The objective was to know and present which were the caracteristics of the children idealized by Arnaldo Barreto and the situation destined to the child of the public paulista primary school. The research was made based on the following sources: books of readings and spelling books produced by Arnaldo Barreto, periodic magazines, journals, decrees and laws and official documents. Subsidized by cultural history, the search is anchored in the representation concept, second to Roger Chartier (1990, 1998, 2001) analizing data contained in books like: instructions given to teachers, contents, illustrations and others, interpreted and analized the sources seeking to court the ideas of Arnaldo Barreto with what was happening at that period, seen that the ideias of this author were inserted in the political and social context of his time. Other concepts ised were: intellectual, childhood and child supported in: Sirinelli (1996, 1998, 2002), Kramer (2007, 2010) and Gouvêa (2004). The results showed that to Arnaldo Barreto it was an obligation to go to school, because in that institution it was taught a good doctrine to clear up the soul making the child educated where the education by the books should awake the interest and the attention of children trough narratives in which the subject was light, joyful, full of unexpected mixed with a good quantity of morality so the school fulfilled its role of insctructing and educating with the finality of forming a child there is virtuous, in other words, obedient, polite, docile, pacient, generous, modest, economic, persevering and ward working, essential caracteristics to the construction of a modern and civilized society. It was verified in the works of Arnaldo Barreto a purpose and targeting in the child as a project of the future, that is related always with the 'molding' in which was subject at childhood. It was established, also, that there were punishments to children that committed some lack or inappropriated behavior at the familiar enviroment our in the academic enviroment pointing to the meed of correcting defects that are impositioned by adults according to their values and society's.